2022
DOI: 10.1088/1361-6587/ac5c11
|View full text |Cite
|
Sign up to set email alerts
|

Halides formation dynamics in nanosecond and femtosecond laser-induced breakdown spectroscopy

Abstract: LIBS is an analytical technique based on the measurement of the emitted radiation coming from a laser-induced plasma (LIP) created after irradiation of a sample by a short duration laser pulse. Research about molecular presence in LIPs has increased because the use of molecular emission has proven an encouraging way to improve LIBS abilities. LIPs are dynamic plasmas with fast time and spatial evolutions, in which atoms and molecules can follow different paths in their evolution and distribution. Molecular cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…51,74 The plasma condition and its evolution in time has been studied under different gas ows; as helium, argon or air; and using different substrates. [75][76][77] The CaF molecular formation has also been studied under helium, 40,73,78 argon 78 and air gas ows. 51,74,78 However, the effect of using 266 nm laser and different gas ows on the CaF LIBS molecular signal from a tooth substrate has not been studied.…”
Section: Spectral Windows Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…51,74 The plasma condition and its evolution in time has been studied under different gas ows; as helium, argon or air; and using different substrates. [75][76][77] The CaF molecular formation has also been studied under helium, 40,73,78 argon 78 and air gas ows. 51,74,78 However, the effect of using 266 nm laser and different gas ows on the CaF LIBS molecular signal from a tooth substrate has not been studied.…”
Section: Spectral Windows Optimizationmentioning
confidence: 99%
“…[75][76][77] The CaF molecular formation has also been studied under helium, 40,73,78 argon 78 and air gas ows. 51,74,78 However, the effect of using 266 nm laser and different gas ows on the CaF LIBS molecular signal from a tooth substrate has not been studied. For all LIBS optimization experiments, the laser spot size and energy were constant at 100 mm and 8 mJ.…”
Section: Spectral Windows Optimizationmentioning
confidence: 99%
“…This conventional LIBS configuration was already used in previous studies and a scheme can be found in ref. 43.…”
Section: Methodsmentioning
confidence: 99%
“…This conventional LIBS conguration was already used in previous studies and a scheme can be found in ref. 43. Each sample spectrum is the result of the in-soware accumulation of 20 spectra from consecutive laser shots, all of them acquired using a grating of 1200 lines per mm positioned to collect light wavelengths between 577 and 610 nm.…”
Section: Libs Setupmentioning
confidence: 99%
See 1 more Smart Citation